Ministerial Decree No. 61/2013 On Amending Certain Provisions of The Statute of Rules Enforcing the Provisions Of Import And Export And The System Of Imported And Exported Commodities Examination And Control Procedures - Egypt (2025)
Ministry of Industry and foreign Trade Decree No. 61 for the Year 2013 on amending certain Provisions of the statute of rules enforcing the provisions of import and export the system of imported and Exported Commodities Examination and Control Procedures وزارة الصناعة والتجارة الخارجية قرار رقم 61 لسنة 2013 فى شأن تعديل بعض أحكام لائحة القواعد المنفذة لأحكام قانون الاستيراد والتصدير ونظام فحص ورقابة السلع المستوردة والمصدرة